2013
DOI: 10.1021/ma401476g
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemical Modification on the Molecular Dynamics of Complex Polyrotaxanes Investigated by Solid-State NMR

Abstract: The chemical modification of the pendant hydroxyl functional groups on cyclodextrins (CDs) significantly suppresses the hydrogen-bonding interactions between the cyclodextrin molecules and leads to the unique viscoelastic properties of hydroxypropylated polyrotaxane (HyPR) [Inomata et al. Macromolecules 2010, 43, 4660–4666]. HyPR consists of poly(ethylene glycol) (PEG) and α-CDs that are partially modified with a hydroxypropyl (Hy) group, setting them apart from other polyrotaxanes (PRs). The molecular dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…In this work, molecular dynamics of the PLA chains in the α′, SC, and glassy samples in a slow dynamic regime for correlation time, 〈τ c 〉, of 10 −3 to 10 2 s are investigated by centerband‐only detection of exchange (CODEX) NMR . The evolution‐time dependence of the CODEX decay curve revealed that PLLA chains in the SC and α′ in addition to the α form exhibit large‐amplitude helical jump motions, similar to those previously observed for several polyolefins and other polymers . Moreover, the temperature dependence of the 〈τ c 〉 values, as determined by mixing‐time dependence CODEX experiments, indicated the kinetics of the molecular motions in three crystalline phases largely different from each other.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…In this work, molecular dynamics of the PLA chains in the α′, SC, and glassy samples in a slow dynamic regime for correlation time, 〈τ c 〉, of 10 −3 to 10 2 s are investigated by centerband‐only detection of exchange (CODEX) NMR . The evolution‐time dependence of the CODEX decay curve revealed that PLLA chains in the SC and α′ in addition to the α form exhibit large‐amplitude helical jump motions, similar to those previously observed for several polyolefins and other polymers . Moreover, the temperature dependence of the 〈τ c 〉 values, as determined by mixing‐time dependence CODEX experiments, indicated the kinetics of the molecular motions in three crystalline phases largely different from each other.…”
Section: Introductionsupporting
confidence: 64%
“…[35] The evolution-time dependence of the CODEX decay curve revealed that PLLA chains in the SC and α′ in addition to the α form [34] exhibit large-amplitude helical jump motions, similar to those previously observed for several polyolefins [4][5][6][7]9,14] and other polymers. [36,37] Moreover, the temperature dependence of the 〈τ c 〉 values, as determined by mixing-time dependence CODEX experiments, indicated the kinetics of the molecular motions in three crystalline phases largely different from each other. Comparisons of the reported crystalline structures and dynamic data obtained during the current study provide detailed information about the relationship between structure and dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The larger hydrophobic surface can then lead to increased interactions with the hydrophobic guest, leading to stronger host-guest complexation. [46][47][48][49][50] Analysis of the results in Fig. 5 indicates that, even though the hydrophilicity of HPαCD is much higher than that of native αCD, host-guest complexation with the copolymer has a lower impact on its T CP .…”
Section: Alpha-cyclodextrin (αCd)mentioning
confidence: 99%
“…Molecular motion plays a critical role in most molecular systems, which may significantly affect the physical, chemical and functional properties of a material. [61][62][63] For example, the mobile components in a multiphase polymer system can significantly increase the toughness of the material, and thus lead to an enhancement of stretching extensibility.…”
Section: Resultsmentioning
confidence: 99%